Komitmen Organisasi Afektif Dan Kepuasan Kerja Sebagai Anteseden Dari Turnover Intention Dengan Moderasi Person-Organization Fit - Wibowo, Frendy, Drs.M. Farid Wajdi,M.M., PhD, Soepatini, S.E., M.Si., Ph.D (2016)
The purpose of this study are: 1) To examine the effect of job satisfaction on turnover intention; 2) To test the effects of affective organizational commitment to turnover intention; 3) To examine the effect of job satisfaction on turnover intention denganperson-organization fit as moderating; and 4) To test the effects of affective organizational commitment to turnover intention with person-organization fit as moderating. This study design using a survey method. The population in this study were all employees Karasidenan Banking in Surakarta. The sample used in this study were 150 employees Karasidenan Banking in Surakarta. In this study the primary data obtained by spreading the questionnaire. Analysis of data using multiple regression analysis (Multiple Regression Analysis) and analysis of the interaction test (Moderated Regression Analysis). The results showed that: 1) Job satisfaction has a negative effect on turnover intention, this indicates that job satisfaction can reduce employee turnover intention; 2) affective organizational commitment has a negative effect on turnover intention, this indicates that affective organizational commitment can decrease employee turnover intention; 3) Person-organization fit moderating effect between job satisfaction on turnover intention, this indicates that the person-organization fit determine the effect of job satisfaction on turnover intention in the company; and 4) Person-organization fit moderating influence between affective organizational commitment to turnover intention, this indicates that the person-organization fit determine the effects of affective organizational commitment to turnover intention in the company. Keywords: job satisfaction, organizational commitment affective, turonver intention, person-organization fit